Changes in Haemostatic Variables Induced by Oral Contraceptives Containing 50 μg or 30 μg Oestrogen: Absence of Dose-dependent Effect on PAI-1 Activity - Scarabin, Pierre-Yves; Plu-Bureau, Geneviéve; Zitoun, Daniéle; Bara, Lucienne; Guize, Louis; Samama, Michel Meyer (Thrombosis and Haemostasis, 1995)
Several studies have suggested a dose-response relation between the oestrogen content of oral contraceptive (OC) and the risk of both venous thrombosis and arterial disease, when oestrogen doses were higher than 50 μg. However, there is no clear epidemiological evidence for a decrease in thrombotic risk with formulations containing less than 50μg oestrogen. Therefore, we investigated haemostatic variables in users of OC containing either 30 μg (35 women) or 50μg (29 women) ethinyl estradiol as compared with non users (64 women) matched for age and smoking status. Mean values of antithrombin activity were significantly lower in 30 γg or 50 μg oestrogen users than in non users (96% and 98% vs 105%, respectively, p<0.001), but they were not significantly different between the two groups of OC users. There was a significant increase in mean values of factor VII antigen in women taking either 30μg or 50μg oestrogen as compared with non users (96% and 101% vs 85%, respectively, p<0.005). Although the difference between both groups of OC users was not significant, a positive linear trend in factor VII levels was observed within the 0-50μg oestrogen range (p <0.001). Mean levels of fibrinogen were slightly higher in 30μg or 50μg oestrogen users than in non users (2.71, 2.66 g/l vs 2.55 g/l, respectively,), but there was no significant difference between the three groups. Mean values of PAI-1 activity were significantly lower in both groups of OC users than in non users (4.89 and 4.63 AU/ml vs 6.47 AU/ml, respectively, p <0.02), but this decrease was not dose-dependent. There was no significant difference in haemostatic variables between 30 μg oestrogen preparations containing either 100μg (13 women), 150μg (3 women) or 200μg (19 women) levonorgestrel. In 50μg oestrogen preparations, the wide range of different types of progestogens did not allow valid assessment of proge- stogens effect. These data provide further evidence for an alteration of blood coagulation and fibrinolysis in OC users within the 30μg-50μg oestrogen range. However, despite a possible dose-dependent effect of oestrogen on factor VII, our results suggest no substantial change in PAI-1 activity and other markers of thrombogenic risk when oestrogen content of combined OC is decreased from 50μg to 30μg. The potential role of progestogens in haemostatic system needs further investigations.